Comparative Analysis of Mined Reserve Tonnage on "M" Hill Between Mine Plan and Mining Realization - Djamaluddin Djamaluddin; Mulhadramy Mulhadramy; Nurliah Jafar (Journal of Geology and Exploration, 2022)
In mining activities, there is often a discrepancy between the plan and actual conditions in the field; if not identified early, this discrepancy will undoubtedly have the potential to cause losses if it continues to repeat itself. This study aimed to determine the factors driving the difference between the mine plan and mining realization. This research uses Pit design data, mine progress measurement data, material movement data, and two mine plan data, namely the backup plan model resulting from detailed exploration and the backup plan model data from the input drill results. From the results of the mine plan research, the closest to realization is the plan using input drill data with an average material movement difference of 10% and the difference in mined ore reserves an average of 12%. In comparison, detailed exploration data with an intermediate material movement difference of 12% to 42% and the contrast in mined ore reserves is 52% on average. The presence of overcuts influences this and the use of different densities.